2018
DOI: 10.2478/emj-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of BIM technology application in project planning

Abstract: The study aimes at identification of the difficulties in choosing the correct concept of the main building process. The use of a proper BIM design may help the user avoid mistakes and make the building process faster as well as less financial resource intensive. The authors focused on literature review, analysing the difficulties of the BIM design software technology in construction project planning. The biggest flaws in BIM design are inherent in three building process stages: 1) the preparation of a building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The aim and benefit of a clear, reliable and usable measurement systems is to provide 'feedback for improvement' and 'guidance for next steps' (Nightingale & Mize, 2002, p. 19) as suggested in the former statements. However, Ustinovičius et al (2018) reaffirms this as merely by stating BIM as a delivery mechanism it doesn't result in 'secured consistency' and therefore applying theoretical BIM without defining approaches attracts inefficiencies (Pidgeon and Dawood, 2021). Also, it is evidenced that when a large number of solutions (or options) are defined, the required evaluation and selection process may become extremely complex and difficult to handle (Cecconi et al, 2017).…”
Section: Fig 2: Ipa Delivery Confidence Assessment (Dca) (Ipa 2020)mentioning
confidence: 99%
“…The aim and benefit of a clear, reliable and usable measurement systems is to provide 'feedback for improvement' and 'guidance for next steps' (Nightingale & Mize, 2002, p. 19) as suggested in the former statements. However, Ustinovičius et al (2018) reaffirms this as merely by stating BIM as a delivery mechanism it doesn't result in 'secured consistency' and therefore applying theoretical BIM without defining approaches attracts inefficiencies (Pidgeon and Dawood, 2021). Also, it is evidenced that when a large number of solutions (or options) are defined, the required evaluation and selection process may become extremely complex and difficult to handle (Cecconi et al, 2017).…”
Section: Fig 2: Ipa Delivery Confidence Assessment (Dca) (Ipa 2020)mentioning
confidence: 99%
“…A selection of some of these academic areas alongside their subject focus can be found below in Table 1, with Table 2 outlining similar approaches but with focus on Industrial literature. Singh et al, 2010;Verkinos, 2015;Da Silva et al, 2019 Return on Investment Eadie et al, 2014;Doloi, 2013;Azhar et al, 2012;Akponeware et al, 2017 BIM v Non-BIM Project Review Barlish and Sullivan (2012) Benefits of BIM Young et al, 2009;Chahrour et al, 2021;Bargstadt, 2015 Lessons Learned and Case Studies Ustinovičius et al, 2018;Wiley et al, 2015;Highways England, 2020 Cultural andBehavioural Changes Latham, 2003;Bargstadt, 2015 Training and Development Needs Hore et al, 2011 Adoption and Implementation of BIM Zuppa et al, 2009;Doloi, 2013;Verkinos, 2015 To date there have been extensive academic and literature research techniques applied, highlighting some of the benefits of BIM such as but not limited to application within 4D construction scheduling (Da Silva et al, 2019), off site construction techniques (Verkinos, 2015) and Clash detection and avoidance (Akponeware et al, 2017;Chahrour et al, 2021).…”
Section: Below)mentioning
confidence: 99%
“…Ustinovičius, et al [5] concluded in 《Challenges of BIM technology application in project planning 》that the proper use of BIM technology design can help users avoid mistakes and reduce the loss of financial resources.…”
Section: Literature Reviewmentioning
confidence: 99%